The Effect of Profit Distribution Management on Islamic Commercial Banks' Performance with Return on Assets as a Moderating Variable - Hadi Purnomo (Yayasan Riset dan Pengembangan Intelektual, 2024)
The purpose of the study is to examine the impact of ROA as a moderator on earnings management, CAR, NPF, TPF. Data from financial reports, obtained through the official website of the Indonesia Stock Exchange (IDX). Sharia Commercial Banks on the IDX in 2017 - 2022 are the research population. The sample size with a purposive sampling technique. Nine BUS with 54 samples. The data analysis technique uses EViews 10, while the research model uses a random effect model. The results of the study are that DPK, CAR, and ROA have a major influence on earnings management. However, NPF has no effect on earnings management. ROA can reduce the impact of DPK and CAR on earnings management. ROA does not moderate the relationship between NPF and earnings management.